RESPON PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq) MAIN NURSERY TERHADAP PENAMBAHAN DOSIS PUPUK HAYATI CAIR DI POLYBAG - Aryani, Ida; Aminah, R. Iin Siti; Priangan, Deri Bakti (Universitas Muhammadiyah Palembang, 2020)
Growth Response Seed Oil Palm (Elaeis guineensis jacq) Main Nursery Against Biological Fertilizer Addition of Liquid Dosage in polybag. This study aims to identify and study the growth response of seedlings of oil palm (Elaeis guineensis Jacq) Main Nursery on the addition of liquid bio-fertilizer in polybag. This research was conducted at the experimental Agro Technology Faculty of Agriculture, University of Palembang and University of Muhammadiyah Palembang in farmer's garden, Sukajaya Village, Sukarame District, Palembang City. Beginning in May to September 2019. This study used non factorial randomized block design with 5 treatments were repeated four times. The treatment is as follows: B0: Without Bio P, B1: 1cc / l of water, B2: 1,5cc / l of water, B3: 2cc / l of water, B4: 2,5cc / l of water, B5: 3cc / l of water. The parameters observed in this study is Added Plant height (cm), Added Total sheaths Leaves (strands), Added length sheaths leaves (cm), Total Roots Primer (strands), Long Roots Primer (cm), Weight Dry Plants (g) , The results showed that treatment Bio fertilizer P with a dose of 2.5 cc / l of water give good growth in plant height increment, the length of the leaf and stem of the plant dry weight, compared with other treatments. Keywords: Palm Oil Seeds, Liquid Biological Fertilizer.